PEMBUATAN VIDEO LIVE SHOOT PENGENALAN PRODI TEKNIK MULTIMEDIA DAN JARINGAN POLIBATAM - Arta Uly Siahaan; Puspoadi Nugroho Pratama (Politeknik Negeri Batam, 2023)
Batam State Polytechnic is one of the public educational institutions inBatam, Riau Islands. It has several departments and study programs. One ofthem is the Informatics Engineering Department, which consists ofInformatics Engineering, Multimedia and Networking, Animation, and CyberSecurity Engineering. However, based on a 2017 survey by IndonesianCareer Center Network (ICCN), 85% of students choose the wrong major. Toovercome this problem,